Preparing a high-quality and impactful sport science manuscript - Pyne, D. (International Journal of Sports Physiology and Performance, 2020)
The articler explains how to prepare a high-quality and impactful sport science manuscript. Three key areas in ensuring a high-quality manuscript are project formulation and design; methodology and analytical issues; and style, clarity, and quality of the written presentation.